(untitled) (PerCursos, 2021)
This article aims to analyze what we theoretically call discursiveness in the texts of the poet Éder Rafael de Araújo. To fulfill this proposal, we carried out, first, reflections on the constitution and development of Brazilian poetry in the second half of the 20th century, as well as its aspects and oppositions. After the brief summary, we will talk about poems, mainly books Eu no mundo que sou no mundo que há em mim and Poesia e revolta, demonstrate how this alleged discursiveness that we call is present in discourse and its importance for the poetic elaboration of Araújo.